Hospital Outcome of Acute Stroke Patients Associated with Various Risk Factors and Co-morbidities (Bangladesh Critical Care Journal, 2022)
Background: Stroke is a global health problem, leading cause of death all over the world. It accounts for chronic illness and disability in a large segment of population. It imposes a great loss on economy of the nation due to loss of service of the workforce during illness and extended hospitalization they require during recovery. Stroke continues to have a great impact on public health. It is associated with multiple risk factors and co-morbid conditions.Objective: To find out the hospital outcome of acute stroke patients associated with various risk factors and co-morbidities.Materials and methods: This is a cross sectional observational study, carried out in the department of Medicine and Neurology, Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh for a period of 6 months. One hundred patients presented with acute stroke diagnosed on clinical & investigational background fulfilling the inclusion and exclusion criteria were enrolled in the study. Stroke severity was assessed using National Institute of Health Stroke Scale (NIHSS) score. Patients’ symptoms, degree of disability or dependence in the daily activities and clinical outcome were evaluated and measured by the modified Rankin Scale (mRS).Result: This study showed that a majority of patients (49%) were in the 51-60 years age group, mean age was 56.81 years. Male and female ratio was 1.38:1. Among all all-risk factors, hypertension is the most common, present in 72% cases; the next most common risk factors were DM (59%), smoking (47%), heart disease (35%), and migraine (14%). About 72% of patients had a mild stroke, 17% of patients had a moderate stroke and 11% of patients had a severe stroke according to NIHSS score at admission. Seventy-four (74%) of them had infarction and the rest had hemorrhage. The study showed that 62% of the patients recovered (mRS score 0 to 2) and among them the maximum were ischemic stroke. 29% had poor outcomes, disabled and they were discharged on request or risk bond (mRS score 3 to 5). 9% expired during hospital stay (mRS score 6). Logistic analysis revealed that age >50 years, hypertension, diabetes mellitus, heart disease, hyperlipidemia, family history of CVD, CAD, past history of stroke / TIA, migraine and peripheral vascular disease were associated with poor stroke outcome.Conclusion: This study shows that the main risk factors & the comorbid conditions for a stroke were hypertension, diabetes mellitus, ischemic heart disease, hyperlipidemia and smoking. People suffering from a stroke with these risk factors have poorer outcomes than those with no risk factors & comorbidities. Identifying characteristics of people at high risk of recurrence has important implications for planning secondary prevention strategies to reduce the disease burden. Early detection and prevention of the risk factors can reduce health care burden and disability.Bangladesh Crit Care J March 2022; 10 (1): 15-18